Evidence-based Enhancement of the Detection, Prevention, and Treatment of Mental Illness in the Connecticut Correction Systems, 2003 - Ford, Julian ([Verlag nicht ermittelbar], 2015)
The study developed and tested the Brief Mental Health Screening Tool to enhance the identification of psychiatric disorders among adult detainees. Participants were randomly recruited within 24 to 72 hours of entering State-run jails in Connecticut. In the first phase, participants completed a 25-minute screening interview, after which 20 percent of the participants were asked to complete a longer interview 1 week later to establish a more detailed account of Axis I and Axis II psychiatric disorders and psychosocial functioning. In a second phase, the new Brief Mental Health Screening Tool was tested and validated on a new sample of participants.